Primary Breast Lymphoma with Aggressive Extranodal Involvement: 18F-FDG PET-CT Findings of Two Unusual Cases (Bangladesh Journal of Nuclear Medicine, 2026)
Background: Primary breast lymphoma (PBL) is a rare extranodal non-Hodgkin lymphoma, accounting for less than 0.5% of all breast malignancies. Due to its rarity and nonspecific clinical and imaging features, diagnosis is often challenging, particularly in cases with dense breast tissue or atypical presentation. This report describes two cases of histologically confirmed PBL with aggressive clinical behavior and extensive systemic involvement. Case Reports: Case1 - A 70-year-old male had bilateral breast enlargement and was diagnosed with diffuse large B-cell lymphoma. Case 2 - A 28-year-old female with dense breast tissues had inconclusive reports in conventional imaging. The biopsy reported plasmablastic lymphoma. Both the patients demonstrated intensely hypermetabolic bilateral breast lesions in 18F-FDG PET-CT with widespread nodal and extranodal involvement, including lymph nodes, lungs, peritoneum, skin, and skeleton, consistent with advanced-stage (stage IV) disease. Conclusion: These cases highlight the aggressive nature of certain PBL subtypes and the limitations of conventional imaging modalities. FDG PET-CT proved essential in accurately staging the disease, detecting multifocal involvement, and guiding clinical management. Early utilization of PET-CT is crucial for comprehensive disease assessment and optimal treatment planning in patients with suspected primary breast lymphoma.Bangladesh J. Nuclear Med. 29(1): 120-124, 2026